Don’t Fake It, Make It! Thriving in Virtual Conferences and Meetings - Lauri M Baker; Matt P. Benge; Anissa Zagonel; Jarred Shellhouse; Cheryl R Boyer; Phillip Stokes (EDIS, 2020)
Our ways of working, meeting, and networking have become more virtual than ever before. This series dives into the preparation needed to host a successful virtual experience, as well as steps participants can take to get the most benefit from a virtual conference or meeting. This series will also help hosts understand the value of online conferences and meetings and demonstrate how to create engagement in an online format. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication, the first in the series, was written by Lauri M. Baker, Matt P. Benge, Anissa Zagonel, Jarred Shellhouse, Cheryl R. Boyer, and Phillip Stokes.